Аналітичний облік як сучасний засіб надання інформації в умовах інформаційної економіки - Кантаєва, О.В. (Культура народов Причерноморья, 2013)
Розглянуто суб’єктивно-об’єктивний зміст трансформації економічної системи, виділені шляхи трансформації: еволюційний, реформаційний та революційний. Досліджено ряд загальних закономірностей, в цілому притаманних трансформаційним економікам. Розглянуто моделі ринкових трансформацій країн Центральної та східної Європи. Виявлені нові вимоги до бухгалтерського обліку, які висуваються суспільством в умовах розвитку інформаційної економіки. Внесено пропозицію щодо перейменування бухгалтерського обліку в аналітичний облік. Рассмотрено субъективно-объективное содержание трансформации экономической системы, выделены пути трансформации: эволюционный, реформационный и революционный. Исследован ряд общих закономерностей, в целом присущих трансформационным экономикам. Рассмотрены модели рыночных трансформаций стран Центральной и восточной Европы. Выявлены новые требования к бухгалтерскому учету, которые выдвигаются обществом в условиях развития информационной экономики. Внесено предложение относительно переименования бухгалтерского учета в аналитический учет. Transformation is a complicated and long-term process, which depends on economic policy, taking into account the dynamic of world economic relations development. These processes are suggested to consider in terms of a subjective-objective content, which enables a comprehensive approach to the macroeconomic policy problems. Transformation methods were marked out in the article: evolutional, reformation, revolutionary. A number of common regularities, appropriate to transformational economies, were researched. The models of market transformation in Central and Eastern Europe were examined. New requirements to the accounting, produced by society in terms of informational economy development, were found out. Drown a conclusion that Ukrainian accounting system transformation process indicates national accounting system harmonization to the international abstract ("capitalist") model. Since modern accounting includes not only collecting and providing information function, new requirements are brought for the control function in the framework of management accounting development, such functions as analysis and management of the gotten information become the most influential, utilization level of information technologies increases, it is suggested to rename accounting into the analytical accounting.